The Effect of the Contaminated Starter with Yeast on the Quality of the Kurdish Fermented Milk (Mast) - Ali, Anwar H.L; Kader, Stara; Hamzah, Hayder M. (Sulaimani Journal for Pure and Applied Sciences, 2009)
Mast is the type of set yoghurt manufactured in Kurdistan, it is firm fermented milk, characterized by yeasty, sharpen acidity and fir m consistency. Applying the same traditional method by using local mast in the Sulaimani city as starter which contains lactic acid bacteria with contaminated yeasts. The starters were divided into four parts, the first one was the control and the other three parts were treated with heat in water bath for (60°C/10 minute, 65°C/10 minute and 65°C/20 minute) respectively. The experiment reported that the control (untreated starter) have the highest yeast cells count (100%), and the starter treated with 65°C/20 minute have the lowest yeast cells count ( 0.3%). The starter treated with 65°C for 10 and 20 minute produces best mast quality according to the sensory test in comparison with other treatments.
Keywords: Fermented milk; heat treatment; lactic acid bacteria; yeast